Addressing the Neuroprotective Actions of Coffee in Parkinson's Disease: An Emerging Nutrigenomic Analysis - Lai Kuan Lee; Nur Anis Raihana Mhd Rodzi (MDPI AG, 2022)
Caffeine is one of the predominant dietary components and psychostimulants present in coffee, a widely appreciated beverage. Corroborating epidemiological and laboratory evidence have suggested an inverse association between the dietary intakes of coffee and the risk of Parkinson's Disease (PD). Growing attention has been paid to the impact of coffee consumption and genetic susceptibility to PD pathogenesis. Coffee is believed to play prominent roles in mediating the gene makeup and influencing the onset and progression of PD. The current review documents a current discovery of the coffee × gene interaction for the protective management of PD. The evidence underlying its potent impacts on the adenosine receptors (A2AR), estrogen receptors (ESR), heme oxygenase (HO), toxicant responsive genes, nitric oxide synthase (NOS), cytochrome oxidase (Cox), familial parkinsonism genetic susceptibility loci, bone marrow stromal cell antigen 1 (BST1), glutamate receptor gene and apolipoprotein E (APOE) genotype expressions is outlined. Furthermore, the neuroprotective mechanisms of coffee for the amelioration of PD are elucidated.